2021
DOI: 10.3201/eid2701.203027
|View full text |Cite
|
Sign up to set email alerts
|

Risk for SARS-CoV-2 Infection in Healthcare Workers, Turin, Italy

Abstract: We measured severe acute respiratory syndrome coronavirus 2 spike protein subunits S1/S2 antibodies by using capillary electrophoresis and a chemiluminescence immunoassay for 5,444 active healthcare workers in Italy. Seroprevalence was 6.9% and higher among participants having contact with patients. Seroconversion was not observed in 37/213 previously infected participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 10 publications
4
36
0
1
Order By: Relevance
“…Both studies were performed in a similar time period to our analysis, as they had a lag of some months from the SARS-CoV-2 spread in the two countries; the first was conducted at the end of January, while the second in April–June. Nevertheless, seroprevalence in our study was higher than those reported by the Italian seroprevalence surveys for comparable group (9.8% in North Italy region) and than those conducted on some Italian hospitals: 4.56% [ 7 ], 5.13% [ 8 ], 6.93% [ 9 ], and 7.43% [ 6 ], while our results are in line with Baracco et al (16.79%) [ 10 ]. The test used in these studies had similar characteristics in terms of sensitivity and specificity, with diagnostic accuracy measures higher than 90%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Both studies were performed in a similar time period to our analysis, as they had a lag of some months from the SARS-CoV-2 spread in the two countries; the first was conducted at the end of January, while the second in April–June. Nevertheless, seroprevalence in our study was higher than those reported by the Italian seroprevalence surveys for comparable group (9.8% in North Italy region) and than those conducted on some Italian hospitals: 4.56% [ 7 ], 5.13% [ 8 ], 6.93% [ 9 ], and 7.43% [ 6 ], while our results are in line with Baracco et al (16.79%) [ 10 ]. The test used in these studies had similar characteristics in terms of sensitivity and specificity, with diagnostic accuracy measures higher than 90%.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, peak of 9.8% in Northern Italian regions was observed among HCWs. Additionally, Italian studies conducted in a specific hospital in Northern Italy showed the percentage of seropositivity to be around 5 to 7% [ 6 , 7 , 8 , 9 ], in line with national seroprevalence. Only one study conducted in Lodi hospital reported higher values (16.8%) [ 10 ].…”
Section: Introductionmentioning
confidence: 88%
“…HCWs ≥50 years old had approximately a three-fold risk of seroconversion compared with HCWs of younger age groups. Also, older HCWs were reported to have higher IgG titres in an Italian HCW cohort ( Calcagno et al, 2021 ) and a higher seroprevalence in Idaho, the USA ( Bryan et al, 2020 ). Having chronic kidney disease was associated with a four-fold risk of seroconversion among HCWs in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For this update, 12 cohort studies ( 3–9 , 11 , 14 , 15 , 18 , 19 ) and 6 cross-sectional studies ( 10 , 12 , 13 , 16 , 17 , 20 ) were added ( Supplement Table 1 ). Four studies were done in the United States ( 4 , 7 , 18 , 20 ), 10 in Europe (Spain [ 5 , 11 , 14 ], Italy [ 8 , 9 ], the United Kingdom [ 12 , 17 ], France [ 13 ], Sweden [ 15 ], and the Netherlands [ 15 ]), 2 in India ( 6 , 10 ), and 1 each in China ( 19 ) and Egypt ( 3 ). As with studies included in prior updates, the studies had methodological limitations, including potential recall bias, low or unclear participation rates, small sample sizes, and potential collinearity.…”
mentioning
confidence: 99%
“…In 4 studies that controlled for confounders, adjusted ORs ranged from 1.92 to 2.79 ( 4 , 12 , 17 , 20 ). Nine new studies reported inconsistent associations between direct patient contact or contact with patients with COVID-19 and risk for SARS-CoV-2 infection or seropositivity primarily based on unadjusted risk estimates ( 3–5 , 7 , 8 , 10 , 14 , 18 , 19 ). In 2 studies that controlled for potential confounders, direct contact with patients with COVID-19 was associated with increased risk for infection versus no contact (adjusted OR, 1.69 [CI, 1.28 to 2.24]) ( 14 ) and versus a nonclinical health care worker role (adjusted OR, 3.08 [CI, 1.09 to 8.78]) ( 13 ).…”
mentioning
confidence: 99%